1984
DOI: 10.1084/jem.159.5.1312
|View full text |Cite
|
Sign up to set email alerts
|

Generation and decay of the immune response to a progressive fibrosarcoma. II. Failure to demonstrate postexcision immunity after the onset of T cell-mediated suppression of immunity.

Abstract: It was shown in the preceding companion paper (1) that early progressive growth of an immunogenic fibrosarcoma results in the acquisition by its syngeneic host of concomitant immunity to growth of a challenge implant, and of tumorsensitized Ly-l-2 + T cells that are capable of adoptively immunizing against an established tumor in y-irradiated recipients. It was shown, in addition, that after the tumor reaches a certain size, concomitant immunity and tumor-sensitized T cells are progressively lost, and that thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 11 publications
1
50
0
Order By: Relevance
“…This could be attributed to the fact that T reg cells return in a tumor-free environment. Studies published 20 years ago show that surgery before the growth of large highly immunogenic tumors prevents the generation of suppressor T cells (45), and more recent work has shown that surgery can reverse immune suppression in tumorbearing hosts (46,47). Indeed, B16 tumors have been shown to recruit T reg cells (48); however, further investigation will be required to determine if surgery prevents the induction of T reg cells that can suppress preprimed memory CD8 T-cell responses.…”
Section: Discussionmentioning
confidence: 99%
“…This could be attributed to the fact that T reg cells return in a tumor-free environment. Studies published 20 years ago show that surgery before the growth of large highly immunogenic tumors prevents the generation of suppressor T cells (45), and more recent work has shown that surgery can reverse immune suppression in tumorbearing hosts (46,47). Indeed, B16 tumors have been shown to recruit T reg cells (48); however, further investigation will be required to determine if surgery prevents the induction of T reg cells that can suppress preprimed memory CD8 T-cell responses.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental evidence suggests that down-regulation of immune response to cancer by concomitant development of suppressor cells may allow progressive local growth of tumors (25). When tumor cells are implanted in mice, an initial slow period of growth is followed by a rapid growth period with local invasion and metastatic spread.…”
Section: Discussionmentioning
confidence: 99%
“…The agonists were delivered early after tumor challenge, and the effects were lost if either CD4 or CD8 T cells were depleted during the priming or effector phases (20,46). The experiments described here occur at times beyond early tumor priming, such that the tumor-bearing animals may already have developed functional effector T cells, albeit within a suppressive environment (47,48). Thus, in these experiments, there was a lesser requirement for CD4 T cells in the response and more of a requirement to overcome CD8 tolerogenic mechanisms.…”
Section: Discussionmentioning
confidence: 99%